Single nucleotide polymorphism array profiling identifies distinct chromosomal aberration patterns across colorectal adenomas and carcinomas. Issue 5 (27th February 2015) - Zarzour, Peter; Boelen, Lies; Luciani, Fabio; Beck, Dominik; Sakthianandeswaren, Anuratha; Mouradov, Dmitri; Sieber, Oliver M.; Hawkins, Nicholas J.; Hesson, Luke B.; Ward, Robyn L.; Wong, Jason W. H.
Abstract : The progression of benign colorectal adenomas into cancer is associated with the accumulation of chromosomal aberrations. Even though patterns and frequencies of chromosomal aberrations have been well established in colorectal carcinomas, corresponding patterns of aberrations in adenomas are less well documented. The aim of this study was to profile chromosomal aberrations across colorectal adenomas and carcinomas to provide a better insight into key changes during tumor initiation and progression. Single nucleotide polymorphism array analysis was performed on 216 colorectal tumor/normal matched pairs, comprising 60 adenomas and 156 carcinomas. While many chromosomal aberrations were specific to carcinomas, those with the highest frequency in carcinomas (amplification of chromosome 7, 13q, and 20q; deletion of 17p and chromosome 18; LOH of 1p, chromosome 4, 5q, 8p, 17p, chromosome 18, and 20p) were also identified in adenomas. Hierarchical clustering using chromosomal aberrations revealed three distinct subtypes. Interestingly, these subtypes were only partially dependent on tumor staging. A cluster of colorectal cancer patients with frequent chromosomal deletions had the least favorable prognosis, and a number of adenomas ( n = 9) were also present in the cluster suggesting that, at least in some tumors, the chromosomal aberration pattern is determined at a very early stage of tumor formation. Finally, analysis of LOH events revealed that copy‐neutral/gain LOH (CN/G‐LOH) is frequent (>10%) in carcinomas at 5q, 11q, 15q, 17p, chromosome 18, 20p, and 22q. Deletion of the corresponding region is sometimes present in adenomas, suggesting that LOH at these loci may play an important role in tumor initiation. © 2015 Wiley Periodicals, Inc.